Effect of Ca2+ doping on the upconversion luminescence properties of NaYF4:Yb3+/Tm3+ nanoparticles and study of its temperature measurement performance. Issue 27 (21st June 2022) - Meng, Mingzhou; Zhang, Rui; Cheng, Zhenlong; Fa, Xinmeng; Yang, Jianghua; Ansari, Anees A.; Ou, Jun; Wurth, Christian; Resch-Genger, Ute
Abstract : NaYF4 :Yb 3+ /Tm 3+ /Ca 2+ nanoparticles with high fluorescence intensity are applied to a sensitive temperature measurement technique with absolute and relative sensitivities as high as 0.0418 K −1 and 2.31% K −1, respectively. Abstract : A solvothermal method was used to prepare a series of Yb 3+ /Tm 3+ /Ca 2+ co-doped NaYF4 nanoparticles with different Ca 2+ contents. Strong upconversion blue fluorescence could be observed under 980 nm laser excitation of the samples. The effect of different Ca 2+ contents on the luminescence intensity was investigated, and it was found that the UV-vis upconversion luminescence increased and then decreased with an increasing Ca 2+ concentration during the increase of the Ca 2+ content from 0 mol% to 25 mol%, reaching the strongest fluorescence at 15 mol%, which was up to about 28 times stronger than that without Ca 2+ doping. Furthermore, the mechanism was investigated, and it was found that the doping of Ca 2+ disrupted the symmetry of the crystal field, resulting in a significant enhancement of the overall fluorescence. Applied to fluorescence intensity ratio thermometry, the absolute and relative sensitivities are as high as 0.0418 K −1 and 2.31% K −1, respectively, with a minimum temperature resolution of 0.0129 K.